A Genetic Marker in the Variable Region of Light Chains of Mouse Immunoglobulins - Edelman, Gerald M. (1970)
A genetic variation was observed upon autoradiographic comparison of tryptic peptide maps of (14)C-labeled normal light chains from 17 different inbred strains of mice. The difference was found in strains AKR/J, C58/J, and RF/J. Chemical analyses showed that the differences were in a region of the amino acid sequence in the neighborhood of half-cystine I of the variable region of the light chain. Breeding experiments showed that the difference segregated in a classical Mendelian fashion.